Effectiveness of Local Supplementary Feeding on Improving Nutritional Status in Malnourished Children - Ega Benita; Sugianti, Ratna; Kusdiyah, Erny (LPPM Universitas Jambi, 2025)
Background: Malnutrition is a deficiency, excess or imbalance in a person's energy and/or nutritional intake. Based on the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of wasting in toddlers is 7.7% and stunting in toddlers is 21.6%. Providing Supplementary Food (PMT) made from local food is one of the strategies for handling nutritional problems in toddlers and pregnant women. Objective: To determine the impact of providing local supplementary feeding (PMT) on cases of undernutrition and severe malnutrition in the working area of Olak Kemang Public Health Center from October 2024 to January 20. Method: This study is descriptive method and uses a mixed-method approach, consisting of interviews and questionnaires. Interviews were conducted with the head of the Olak Kemang Public Health Center, nutrition officers and mothers of toddlers. The questionnaire was given to mothers of toddlers whose children experienced weight stagnation and malnutrition. Result: From 25 respondents and interviews with the head of Olak Kemang public health center and nutrition officers, several factor were identified as contributing to impact of providing local supplementary feeding on malnutrition in the working area of Olak Kemang Public Health Center. These include the increase in weight-for-age (W/A) in toddlers receiving supplementary feeding (PMT) was not significant compared to the increase in weight-for-height (W/H) based on Olak Kemang Health center reporting and recording data. Conclusion: The study found that the prioritized issue was the increase in weight-for-age (W/A) in toddlers receiving supplementary feeding (PMT) was not significant compared to the increase in weightfor-height (W/H).